2022
DOI: 10.1038/s41431-022-01065-2
|View full text |Cite
|
Sign up to set email alerts
|

Participant experiences of genome sequencing for rare diseases in the 100,000 Genomes Project: a mixed methods study

Abstract: In this mixed methods study, a survey and in-depth interviews were used to explore whether decision regret and the psychological impact of receiving genome sequencing (GS) results differed between parents and patients, and between those who received a genetic diagnosis and those who did not. Participants (n = 77) completed a survey that included the Decisional Regret Scale (DRS) and an adaptation of the Multidimensional Impact of Cancer Risk Assessment (MICRA) at least 12 months after consenting for GS for rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…Specifically, participants were unsure whether they were supposed to remain in contact with the UDP and/or felt like the UDP had not explored every possible option to find a diagnosis. Those who remained undiagnosed also expressed disappointment with the lack of diagnosis, similar to previous studies (Mollison et al, 2019; Peter et al, 2022). However, other research indicates patients and parents of patients felt receiving genome sequencing (GS) or exome sequencing (ES) was the final option for them, with individuals experiencing closure whether or not they received a diagnosis (Halverson et al, 2016; Liang et al, 2021; Mollison et al, 2019; Rosell et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Specifically, participants were unsure whether they were supposed to remain in contact with the UDP and/or felt like the UDP had not explored every possible option to find a diagnosis. Those who remained undiagnosed also expressed disappointment with the lack of diagnosis, similar to previous studies (Mollison et al, 2019; Peter et al, 2022). However, other research indicates patients and parents of patients felt receiving genome sequencing (GS) or exome sequencing (ES) was the final option for them, with individuals experiencing closure whether or not they received a diagnosis (Halverson et al, 2016; Liang et al, 2021; Mollison et al, 2019; Rosell et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Additional studies of UDN participants have focused on specific psychosocial characteristics, including anxiety, depression, and empowerment. Patients and parents of patients were given surveys to assess these psychosocial characteristics, which showed lower empowerment scores in adults with undiagnosed diseases compared with parents of children with undiagnosed diseases, as well as higher rates of anxiety, depression, stress, and helplessness in parents of children with undiagnosed diseases (Aldiss et al, 2021; McConkie‐Rosell et al, 2018; Palmer et al, 2018; Peter et al, 2022). These findings are similar to those of individuals with diagnosed genetic conditions and provide an initial impression of the psychosocial characteristics of the rare disease population.…”
Section: Introductionmentioning
confidence: 99%
“…The reasoning they offered for this was that they had had high expectations that a diagnosis, or at least a VUS, would be achieved with WES. The finding that disappointment occurs, or even increases, when persons have heightened or unrealistic expectations about the type of result they will receive, is consistent with insights of other empirical studies and points to acknowledging expectation management as part of the informed consent process (Bos & Bunnik, 2022;Donohue et al, 2021;Eichinger et al, 2023;Peter et al, 2022;Wynn et al, 2018). However, our results show that this observation should be built upon further, since parents who adopted a hopeful stance about what WES might offer them reported being ultimately more satisfied with the whole sequencing experience than the couple in our study who expected a certain outcome or answers from WES and thus reported being disappointed.…”
Section: Discussionsupporting
confidence: 81%
“…Existing studies have suggested that patient concerns include data protection, privacy, and lack of definitive clinical answers 12,13 . Outside the prenatal setting, it has been shown that parents and children taking part in ES for the 100,000 Genomes Project have positive views on research, data sharing, and the healthcare system 13 .…”
Section: Introductionmentioning
confidence: 99%